Estimating Key Largo woodrat abundance using spatially explicit capture–recapture and trapping point transects. (17th April 2016) - Potts, Joanne M.; Buckland, Stephen T.; Thomas, Len; Savage, Anne
ABSTRACT: The Key Largo woodrat ( Neotoma floridana smalli ) is an endangered rodent with a restricted geographic range and small population size. Establishing an efficient monitoring program of its abundance has been problematic; previous trapping designs have not worked well because the species is sparsely distributed. We compared Key Largo woodrat abundance estimates in Key Largo, Florida, USA, obtained using trapping point transects (TPT) and spatially explicit capture–recapture (SECR) based on statistical properties, survey effort, practicality, and cost. Both methods combine aspects of distance sampling with capture–recapture, but TPT relies on radiotracking individuals to estimate detectability and SECR relies on repeat capture information to estimate densities of home ranges. Abundance estimates using TPT in the spring of 2007 and 2008 were 333 woodrats (CV = 0.46) and 696 (CV = 0.43), respectively. Abundance estimates using SECR in the spring, summer, and winter of 2007 were 97 (CV = 0.31), 334 (CV = 0.26), and 433 (CV = 0.20) animals, respectively. Trapping point transects used approximately 960 person‐hours and 1, 010 trap‐nights/season. Spatially explicit capture–recapture used approximately 500 person‐hours and 6, 468 trap‐nights/season. Significant time was saved in the SECR survey by setting large numbers of traps close together, minimizing time walking between traps. Trapping point transects were practical to implement in the field, and valuable auxiliary information on Key Largo woodrat behavior was obtained via radiocollaring. In this particular study, detectability of the woodrat using TPT was very low and consequently the SECR method was more efficient. Both methods require a substantial investment in survey effort to detect any change in abundance because of large uncertainty in estimates. © 2016 The Wildlife Society.